La necesidad de estudiar la insuficiencia del régimen jurídico de la mora y sus efectos implícitos en el código civil Ecuatoriano. - Saraguro Cueva, René Francisco (2011)
I consider to the Moor like the guilty retard in the execution of an obligation, since the simple non guilty retard in the execution of an obligation doesn’t have artificial transcendency. In the face of this consideration I believe necessary the Moor should be studied in what you/they concern to the elements that configure the nonfulfillment of the obligations that the Moor constitutes that can belong to the debtor or of the creditor and the juridical effects that this nonfulfillment brings I get. Many of the contracts and many of the obligations that are contemplated in our Civil Code and that they are reflected in the daily activity of the great majority of people they have been constituted in Moorish whose percentage is considerable. In some cases for the debtor’s blame that is who is prone to be framed inside this artificial figure. And in other cases although in a percentage not so high for the creditor’s blame who has been refused to accept the payment offered by interests personnels causing in this way that the debtor incurs in Moorish. But, is it really enough the juridical régime that outlines the Civil Code, to punish people that incur in Moorish?. Or he/she should modify these dispositions and to be punished in a more coercive way this nonfulfillment. To settle down which the best option is, I have intended to investigate the present he/she fears and this way to focus the most appropriate way to solve this problem and to protect the creditor’s so much interests, as of the debtor that you/they are the entities of the development. I will define to the Moor like the guilty retard in the execution of an obligation, since the simple retard non culprit doesn’t have artificial transcendency. It corresponds the creditor or the debtor in Moor to produce the test that she is not attributable to their blame neither their deceit. The Moor solvendi should be distinguished you/he/she lives of the debtor, of the Moor accipiendi you/he/she lives of the creditor. However in our Civil Code it is determined only when the debtor is in Moorish, article 1567, or when none of the contracting parties is in Moorish, article 1568, but not when the creditor is in Moorish, contrary to other Codes that establish diverse conditions to constitute in Moorish to the creditor or the debtor.